Ramification of thermal expansion mismatch and phase transformation in TiC-particulate/SiC-matrix ceramic composite. Issue 12 (15th August 2020) - Magnus, Carl; Sharp, Joanne; Ma, Le; Rainforth, W.M.
Abstract: This article presents a microstructural study on the role of incipient residual stress relaxation in TiC-particulate/SiC-matrix ceramic composite toughened by thermal expansion mismatch and phase transformation toughening. Exhaustive microstructural studies was undertaken using scanning electron microscopy and transmission electron microscopy following a wear test. It was found that the superposition of hydrostatic tensile stress induced at the surface following the sliding contact on the inherent residual stresses locked in the composite led to a relaxation and/or reduction in the residual stresses. Stress relaxation presented a wider implication for the tribological properties of this ceramic matrix composite (CMC) in the form of a grain-scale rippling microstructural phenomena.